Integrasi Model PCK pada Pengembangan Modul Matematika untuk Mengembangkan Keterampilan Berpikir Kritis - Hapsari Dika Pratiwi; Riawan Yudi Purwoko; Erni Puji Astuti (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2018)
The purpose of this study is to compile a mathematical module that integrates Pedagogical Content Knowledge (PCK) models to develop critical thinking skills of high school students. The development model used in this study is the Plomp development model. Plomp development model consists of 4 stages, namely (a) Investigation Stage, (b) Designing Stage, (c) Realization / Construction Stage, (d) Test Stage, Evaluation, and Revision. The method used to collect data is questionnaire, observation, test of learning outcomes, and documentation. The instruments used were validity sheets, practicality sheets, and effectiveness sheets. Modules are said to be feasible if it meets the criteria Â of valid, practical and effective. Data analysis techniques used are qualitative descriptive analysis techniques. After data analysis, product validity assessment was categorized as very good with an average percentage of 85,15%, practicality assessment categorized as good with a percentage of 76,67%, and effectiveness assessment categorized as good with a percentage of 64,5%. Based on this, it can be concluded that the mathematics module that integrates the PCK model is appropriate to be used to develop critical thinking skills of senior high school students.